ANALISIS DISIPLIN KERJA PEGAWAI DI KOMISI PEMILIHAN UMUM (KPU) KOTA BANJARMASIN - Ella Vironika (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2019)
The purpose of the study was to find out the description of Employee Discipline in the Banjarmasin City General Election Commission (KPU) and what were the obstacles to Employee Discipline in the Banjarmasin City General Election Commission (KPU). The research method uses a qualitative approach with descriptive research types. Data is collected by data sources to informants. Using interview data collection techniques and documentation. Data analysis used descriptive analysis, namely a description in the form of a description to explain the answers given by respondents, the data obtained through interviews and literature was used as supporting data to strengthen and deepen the results obtained. The results showed that the work discipline of employees at the Banjarmasin City General Election Commission (KPU) had gone well. Evidenced by the presence of employees who come every day on time, permission to leave during working hours, work home on time and do not miss work. The employee always obeys work rules, adheres to work standards with the intention of always being responsible for the mandated task. In carrying out their duties always carefully and thoroughly and have a good work ethic.